Biomechanics Analysis During Cutting Oil Palm Fronds - Narendaran, Harisangar (Universiti Sains Malaysia, 2021)
The study discusses about lumbar load analysis during cutting oil palm fronds. Initially, oil palm workers were conducting multiple works in the oil palm field. Due to their labour intense work, workers experience musculoskeletal disorders and injuries. Since these disorders occurs during work, they are called as Work-related Musculoskeletal Disorders (WMSDs) Previously, these risks and cause of injuries were inspected using ergonomic assessment tools such as Rapid Entire Body Assessment (REBA), Ovako Working posture Assessment System (OWAS) and Rapid Upper Limb Assessment (RULA). Due to their limitations in assessment such as not accounting working time and forces workers are dealing, these tools were less efficient. Furthermore, these tools were only conducted assessment based on observation. Possibility of error to occur is very high. Therefore, inertial measurement unit (IMU) and force plate is used to measure body postures. IMU used is Xsens attached to two subject’s body. Different height for chisel is used and two types of sickles were used for cutting of fronds. Subject will perform cutting and pruning from a platform which have force plate. The whole activity will be recorded through phone camera for processing. After Xsens data and force plate’s data are processed, graph of REBA and time is produced. Based on the graphs, high REBA scored posture with high hand load was opted out for lumbar and shear compression using 3D Static Strength Prediction Program (3DSSPP) software. Lumbar compression and shear values were identified. The necessary of bioassessment using IMU is defined.